Evaluation of WC-17Co and WC-10Co-4Cr thermal spray coatings by HVOF on the fatigue and corrosion strength of AISI 4340 steel - Voorwald, HJC; Souza, R. C.; Pigatin, W. L.; Cioffi, MOH (Elsevier B.V., 2005)
It is known that chromium electroplating is related to the reduction in the fatigue strength of base metal. However, chromium results in protection against wear and corrosion combined with chemical resistance and good lubricity. Environmental requirements are an important point to be considered in the search for possible alternatives to hard chrome plating. Aircraft landing gear manufactures are considering WC thermal spray coating applied by the high-velocity oxygen-fuel (HVOF) process an alternative candidate, which shows performance at least comparable to results, obtained for hard chrome plating. The aim of this study is to compare the influence of WC-17Co and WC-10Co-4Cr coatings applied by HVOF process and hard chromium electroplating on the fatigue strength of AISI 4340 steel, with and without shot peening. S-N curves were obtained in axial fatigue test for base material, chromium plated and tungsten carbide coated specimens. Tungsten carbide thermal spray coating results in higher fatigue strength when compared to hard chromium electroplated. Shot peening prior to thermal spraying showed to be an excellent alternative to increase fatigue strength of AISI 4340 steel. Experimental data showed higher axial fatigue and corrosion resistance in salt fog exposure for samples WC-10Co-4Cr HVOF coated when compared with WC-17Co. Fracture surface analysis by scanning electron microscopy (SEM) indicated the existence of a uniform coverage of nearly all substrates. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: fatigue; corrosion; thermal spray; AISI 4340 steel